2001
DOI: 10.1002/jqs.649
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene dinoflagellate cysts as indicators for short‐term climate variability in the eastern Laptev Sea (Arctic Ocean)

Abstract: Kunz-Pirrung, M., Matthiessen, J. and de Vernal, A. 2001. Late Holocene dinoflagellate cysts as indicators for short-term climate variability in the eastern Laptev Sea (Arctic Ocean).ABSTRACT: A sediment sequence from the eastern Laptev Sea shelf (Siberian Arctic, Russia) has been studied for dinoflagellate cysts in order to reconstruct sea-surface conditions during the late Holocene. Variability of assemblage composition and derived sea-surface temperature estimates indicate that the neoglacial cooling was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The primary micropalaeontological data – dinocyst assemblages (relative abundances; Figure 5) – agree well with the P B IP 25 sea-ice regimes (Figure 4). The interval prior to AD 1740 is characterized by a high proportion of autotrophs (particularly O. centrocarpum sensu Wall and Dale (1966)), whose producers require seasonally open water for photosynthesis (and are generally distributed along the inflow of relatively warmer waters within an Arctic context; Kunz-Pirrung et al, 2001; Matthiessen et al, 2005) and a reduced component of heterotrophs found in regions characterized by extended SIC (producing dinocysts such as I. ? cezare ; De Vernal et al, 2013b; Zonneveld et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary micropalaeontological data – dinocyst assemblages (relative abundances; Figure 5) – agree well with the P B IP 25 sea-ice regimes (Figure 4). The interval prior to AD 1740 is characterized by a high proportion of autotrophs (particularly O. centrocarpum sensu Wall and Dale (1966)), whose producers require seasonally open water for photosynthesis (and are generally distributed along the inflow of relatively warmer waters within an Arctic context; Kunz-Pirrung et al, 2001; Matthiessen et al, 2005) and a reduced component of heterotrophs found in regions characterized by extended SIC (producing dinocysts such as I. ? cezare ; De Vernal et al, 2013b; Zonneveld et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Dinocysts are only indirectly influenced by sea ice. Autotrophs such as O. centrocarpum need seasonally open water for photosynthesis (Kunz-Pirrung et al, 2001; Matthiessen et al, 2005). Conversely, heterotrophs (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were grouped together into Echinidinium-Islandinium complex. Islandinium minutum is the more specific taxa of shelf assemblages of the Arctic Ocean, including polynyas (Kunz-Pirrung et al, 2001). It is an euryhaline taxon dominating assemblages from the continental margins where summer temperatures rarely exceeding 7 °C ranging from −2 to 5 °C and salinity varies between 17 to 34 PSU.…”
Section: Ecology Of Dinoflagellate Assemblagesmentioning
confidence: 99%
“…So far, there was little data available on past hydrology from the Laptev Sea due to a scarcity of sediment cores and the lack of reliable age control of these cores [ Holmes and Creager , 1974; Aksenov et al , 1987]. Recent micropaleontological studies now indicate that groups such as diatoms and aquatic palynomorphs offer the opportunity to also investigate past hydrological processes [ Bauch et al , 2000; Bauch and Polyakova , 2000; Kunz‐Pirrung et al , 2001].…”
Section: Introductionmentioning
confidence: 99%